2017
DOI: 10.1177/1049909117730555
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Review of the Literature on Hispanics and Hospice

Abstract: The provision of optimal end-of-life care to Hispanics receiving hospice care requires familiarity with hospice-specific variables. For example, a preference for nondisclosure of terminal prognosis in some Hispanics is incongruous with traditional hospice practice. In addition, the Spanish word for hospice, "hospicio," has negative connotations about abandonment of loved ones. Added to cultural considerations are socioeconomic considerations. Many marginalized Hispanic individuals may experience distinct chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
(168 reference statements)
0
13
0
Order By: Relevance
“…It is sometimes assumed that racial or ethnic minority groups do not prefer direct communication about difficult health-related news, but our findings show diversity within racial and ethnic groups. 21 -23 One African American participant explained, “I ask point blank, ‘Is he going to die?’ ‘Is she going to die?’ But they don’t tell you that. […] The relationship with the doctor is very important, you know, that you want to be able to talk freely with the person and get good care answers.” While direct communication from providers was a strong theme across all groups, the nature and amount of medical information a participant desired varied widely by individual, regardless of race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is sometimes assumed that racial or ethnic minority groups do not prefer direct communication about difficult health-related news, but our findings show diversity within racial and ethnic groups. 21 -23 One African American participant explained, “I ask point blank, ‘Is he going to die?’ ‘Is she going to die?’ But they don’t tell you that. […] The relationship with the doctor is very important, you know, that you want to be able to talk freely with the person and get good care answers.” While direct communication from providers was a strong theme across all groups, the nature and amount of medical information a participant desired varied widely by individual, regardless of race/ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…First, in contrast to a common assumption that members of racial and ethnic minority groups do not prefer direct communication about their illness, we found that participants in all groups expressed a preference for open, honest communication. 21 -23 That is not to say that all participants agreed with this or that these participants represented all people from these groups. However, it does show that there is diversity within racial and ethnic groups, and research and practice should acknowledge that diversity within groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34−36 The patient's son's reference to previous culturally incongruent interactions warrants consideration of the role for improved care and proactive communication (in the family's chosen language) partnered with cultural humility. 37 Ms. B's son has experienced care inequities in the past which warrant a trauma-informed compassionate consideration to the family's current hospice experience. 38,39 Hospice Goals.…”
Section: Ethics Analysismentioning
confidence: 99%
“…2,4,5 The structure and organization of hospice service delivery may contribute to these problematic patterns of service utilization, including issues with language interpretation and cultural insensitivity among hospice providers. 6,7 These issues have prompted calls for more culturally competent care for people nearing the end of life. 8 There are more than 6.5 million adults in the United States with heart failure and this population represents a growing share of hospice patients overall.…”
Section: Introductionmentioning
confidence: 99%